HUBUNGAN POLA MAKAN DENGAN KEJADIAN NYERI LAMBUNG PADA MAHASISWA IKM UNIMA ANGKATAN 2022 - Rezki Amalia Latif (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2024)
Diet is a method or effort to regulate the amount, frequency and type of food with descriptive information including maintaining health, nutritional status, preventing or helping cure disease. Gastric pain is pain or discomfort that occurs in the stomach area, especially in the upper part of the stomach, which is usually related to problems with the stomach or digestive system. One of the factors that causes students to develop stomach pain or gastritis is improper eating patterns. The aim of this research was to determine the relationship between eating patterns and the incidence of stomach pain in IKM Unima 2022 students. The method used was quantitative research using descriptive methods and a cross-sectional approach. The population in this study was 146 and the sample was 107 respondents with data analysis using SPSS version 2022. The research shows a relationship between diet and the incidence of stomach pain in public health students, where the chi-square test results ρ-value 0.028 < α 0.05. It can be concluded that there is a relationship between eating patterns and the incidence of stomach pain in IKM Unima 2022 students.